Importance Performance Analysis (IPA) on Website Quality (Webqual): An Evidence from A Higher Education Institution in Indonesia - Maryana, Lina; Komaladewi, Rita; Mulyana, Asep; Saefullah, Kurniawan (Advances in Social Sciences Research Journal, 2022)
This paper attempts to evaluate the quality of website of the Faculty of Economics and Business of University X in Indonesia, using the WebQual model and map it using Importance Performance Analysis. The study uses a quantitative method of Importance Performance Analysis (IPA), by using an online survey with a WebQual questionnaire. Samples were collected through an accidental sampling, involved 70 samples, collected from the stakeholder of the faculty, representing students, lecturers, partners as well as general public. The result of the study reveals that Information Quality poses the most performed of the Website Quality while Usability was the least ones. The result recommends any higher education institution to evaluate information provided in their website to its stakeholder, should consider its usability as it is the most important factor which is needed by website visitors.